Hyper-damping properties of a stiff and stable linear oscillator with a negative stiffness element - Antoniadis, I.; Chronopoulos, Dimitrios; Spitas, V.; Koulocheris, D. (Elsevier, 2015)
A simple, stiff, statically and dynamically stable linear oscillator incorporating a negative stiffness element is used as a template to provide a generic theoretical basis for a novel vibration damping and isolation concept. This oscillator is designed to present the same overall static stiffness, the same mass and to use the same damping element as a reference classical linear SDoF oscillator. Thus, no increase of the structure mass or the viscous damping is needed, as in the case of a traditional linear isolator, no decrease of the overall structure stiffness is required as in the case of ’zero-stiffness’ oscillators with embedded negative stiffness elements. The difference from these two templates consists entirely in the proper redistribution and reallocation of the stiffness and the damping elements of the system. Once such an oscillator is optimally designed, it is shown to exhibit an extraordinary apparent damping ratio, which is even several orders of magnitude higher than that of the original SDoF system, especially in cases where the original damping of the SDoF system is extremely low. This extraordinary damping behaviour is a result of the phase difference between the positive and the negative stiffness elastic forces, which is in turn a consequence of the proper redistribution of the stiffness and the damping elements. This fact ensures that an adequate level of elastic forces exists throughout the entire frequency range, able to counteract the inertial and the excitation forces. Consequently, a resonance phenomenon, which is inherent in the original linear SDoF system, cannot emerge in the proposed oscillator. The optimal parameter selection for the design of the negative stiffness oscillator is discussed. To further exhibit the advantages that such a design can generate, the suggested oscillator is implemented within a periodic acoustic metamaterial structure, inducing a radical increase in the damping of the propagating acoustic waves. The concept may find numerous technological applications, either as traditional vibration isolators, or within advanced composite materials and metamaterials.